2007
DOI: 10.1007/s11661-007-9225-3
|View full text |Cite
|
Sign up to set email alerts
|

Gigacycle Fatigue Properties of High-Strength Steels According to Inclusion and ODA Sizes

Abstract: Gigacycle fatigue tests were conducted for several versions of JIS-SCM440 low-alloy and JIS-SUJ2 bearing steels using 20-kHz ultrasonic fatigue testing to elucidate the relationship of the inclusion size and type to fish-eye fracture properties. The total number of tested specimens was over 200. Most of the specimens revealed Al 2 O 3 or (Cr, Fe) 3 C inclusion-originating types of fisheye fractures, while TiN inclusions and the matrix also caused fish-eye fractures in some specimens. Based on these fatigue tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 22 publications
4
46
1
Order By: Relevance
“…This influence of crack initiation mechanism on VHCF properties is well in accordance with the literature. For high carbon-chromium steel SUJ2, Furuya et al [32] found longer lifetimes and higher endurance limits for specimens featuring crack initiation at Al 2 O 3 -inclusions and interface fracture than for specimens with (Cr,Fe)C-inclusions where the fractured particles acted as crack starters. For the same high carbon-chromium steel, Spriestersbach et al [33] found higher necessary stress intensity amplitudes to propagate a crack to fracture in the VHCF regime, when the crack started at a fractured interface between AlCaO-or CaO-inclusions and matrix than when it started at a fractured TiNinclusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This influence of crack initiation mechanism on VHCF properties is well in accordance with the literature. For high carbon-chromium steel SUJ2, Furuya et al [32] found longer lifetimes and higher endurance limits for specimens featuring crack initiation at Al 2 O 3 -inclusions and interface fracture than for specimens with (Cr,Fe)C-inclusions where the fractured particles acted as crack starters. For the same high carbon-chromium steel, Spriestersbach et al [33] found higher necessary stress intensity amplitudes to propagate a crack to fracture in the VHCF regime, when the crack started at a fractured interface between AlCaO-or CaO-inclusions and matrix than when it started at a fractured TiNinclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Equations used to predict the VHCF strength typically consider the projected area of the inclusion and the Vickers hardness of the matrix [31]. More recent investigations show, however, that also the type of inclusion is important for the harmful influence of inclusions on VHCF strength [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…When using conventional specimens, however, the difference between the two materials is small, so the results from conventional specimens tend to be misleading, as seen in our past research. 28) Hence, using larger specimens is strongly advisable to be able to correctly evaluate the gigacycle fatigue properties of highstrength steel. This also applies to the evaluation of inclusion sizes when an inclusion inspection employs fatigue testing.…”
Section: Discussionmentioning
confidence: 99%
“…One study indicated that the gigacycle fatigue strength of double-melted and single-melted steels were equivalent in spite of the fact that double-melting reduces inclusions. 28) This result perhaps needs review using larger specimens, since conventional specimens are less reliable. The author already has the test results for single-melted steel, 25) so the review would be achieved by simply adding the new results for double-melted steel.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is commonly believed that the maximum inclusion size exists, below which no crack would initiate at inclusions. The maximum inclusion sizes are 5 lm [38], 8 lm [39] and 15 lm [40] for different steels tested in air. Yang et al [41] proposed an empirical expression to calculate the maximum size for high strength steel, i.e.…”
Section: Fractography For Specimens Tested In Environmental Mediamentioning
confidence: 99%